Long noncoding RNA PCAT6 inhibits colon cancer cell apoptosis by regulating anti-apoptotic protein ARC expression via EZH2. Issue 1 (2nd January 2019) - Huang, Weimei; Su, Geng; Huang, Xiaoxian; Zou, Angru; Wu, Jingfang; Yang, Yunchu; Zhu, Yaru; Liang, Shumei; Li, Deyu; Ma, Feng; Guo, Linlang
ABSTRACT: Prostate cancer-associated ncRNA transcript 6 (PCAT6) is a long intergenic noncoding RNA that is involved in the progression of prostate and lung cancer, acting as a potential diagnostic and prognostic biomarker in nonsmall cell lung cancer. However, little is known about PCAT6 expression and its clinical significance in colon cancer. Here, we aimed to investigate the clinical significance of PCAT6 in colon cancer and its underlying mechanism. The expression of PCAT6 was analyzed in colon cancer tissues using public databases, and a series of in vitro and in vivo experiments was performed to investigate the biological functions of PCAT6 in colon cancer cells and the underlying mechanisms. Our results demonstrated that PCAT6 was upregulated in colon cancer tissues compared with that in noncancerous tissues, correlating with poorer clinical stages and a worse survival status. In vitro and in vivo experiments illustrated PCAT6 promoted cell growth and inhibited cell apoptosis in colon cancer. Mechanistically, PCAT6 enhanced the coenrichment of EZH2 and H3K4me3 at the apoptosis repressor with caspase recruitment domain (ARC) genomic region, promoting the transcriptional activity of ARC. Our data highlighted that PCAT6 acts as a key activator of ARC expression by forming a complex with EZH2, inhibiting cell apoptosis and contributing to colon cancer progression. These findings elucidated that PCAT6 may be a novel prognostic predictor and therapeutic target of colon cancer.